The renewed case for farmers' cooperatives: Diagnostics and implications from Ghana - Francesconi, Gian Nicola; Wouterse, Fleur Stephanie (International Food Policy Research Institute, 2011)
This study presents a stylized but insightful diagnostic of the problems limiting collective action in Ghanaian farmer-based organizations (FBOs). In our analysis, we use a structure-conduct-performance framework, econometrics, and new primary data for 500 FBOs collected through surveys and games. We find that most Ghanaian FBOs are inactive, failing to mobilize their members into any sort of collective action. To understand why this is so, we postulate that in rural Ghana, four typologies can be used to classify FBOs and to distinguish them on the basis of their membership structure and rules of conduct. We then show that FBOs fail to mobilize collective action whenever their structure and conduct are not aligned. In particular, misalignment leads mainly to problems of access to external credit and to a lesser extent to problems of internal cohesion. To maximize collective action, this study recommends the diversification of policy through recognizing the four different types of FBOs, each facing particular and to some extent opposing problems.